Modern methods of processing and creating a digital terrain model (Journal of Geography and Environmental Management, 2018)
Nowadays the requirements for topographic and geodetic products are becoming more important and gaining direct economic importance due to the high rate of market development. The main requirement remains the reliability and differentiation of the results of cartographic materials, and the most important issue is the accuracy of the developed products. The accuracy is affected by a variety of factors, depending both on the means of measurement and the type of processing. This paper presents an overview of modern survey methods for the projecting of linear structures based on the example of road sections in Almaty. Currently, the design of roads is, as a rule, based on topographic survey data, performed by traditional geodetic instruments. It is necessary to apply the automatic projecting system containing components of software, information, technical and organizational support to increase the quality of solutions on projecting objects. This article considers automated approaches for efficient data processing, comparative analysis of software complexes that are widely used to create digital terrain models, their ability to support and create three-dimensional models, import of point cloud, a way of constructing relief, importing and processing initial data.